Multi-level barriers and facilitators to implementing evidence-based antipsychotics in the treatment of early-phase schizophrenia - Carroll, Allison J.; Robinson, Delbert G.; Kane, John M.; Kordon, Avram; Bannon, Jennifer; Walunas, Theresa L.; Brown, C. Hendricks (Frontiers in Health Services, 2024)
IntroductionLong-acting injectable (LAI) antipsychotic medications and clozapine are effective yet underutilized medical therapies in early intervention services. The purpose of this study was to conduct a pre-implementation evaluation of contextual determinants of early intervention programs to implement innovations optimizing LAI antipsychotic and clozapine use within a shared decision-making model.MethodsSemi-structured interviews explored barriers and facilitators to implementing LAI antipsychotics and clozapine in early intervention services. Participants were: prescribers (n = 2), non-prescribing clinicians (n = 5), administrators (n = 3), clients (n = 3), and caregivers (n = 3). Interviews were structured and analyzed using the Consolidated Framework for Implementation Research (CFIR 2.0).ResultsParticipants were supportive of using LAI antipsychotics, despite barriers (e.g., transportation, insurance coverage), while most were unfamiliar with clozapine (Innovation). Critical incidents (e.g., COVID-19) did not interfere with implementation, while barriers included lack of performance measures; stigma affecting willingness to take medication; and clozapine considered to be a “last resort” (Outer Setting). Treatment culture was described as client-centered and collaborative, and most participants indicated LAI antipsychotic use was compatible with clinic workflows, but some were in need of resources (e.g., individuals trained to administer LAI antipsychotics; Inner Setting). Participants on the healthcare team expressed confidence in their roles. Family education and collaborative decision-making were recommended to improve client/family engagement (Individuals). Participants related the importance of tracking medication compliance, addressing client concerns, and providing prescribers with updated guidelines on evidence-based treatment (Implementation Process).DiscussionResults may guide implementation strategy selection for future programs seeking to optimize the use of LAI antipsychotics and clozapine for early-phase schizophrenia, when appropriate.